Machine learning prediction of postoperative unplanned 30-day hospital readmission in older adult - Li, Linji; Wang, Linna; Lu, Li; Zhu, Tao (Frontiers in Molecular Biosciences, 2022)
Background: Although unplanned hospital readmission is an important indicator for monitoring perioperative quality of hospital care, few published studies of hospital readmission have focused on surgical patient populations, especially in the elderly. We aimed to investigate if machine learning approaches can be used to predict postoperative unplanned 30-day hospital readmission in old surgical patients. Methods: We extracted demographic, comorbidity, lab, surgical, medication data of elderly patients older than 65 who underwent surgeries under general anesthesia in West China Hospital, Sichuan University from July 2019 to February 2021. Different machine learning approaches were performed to evaluate whether unplanned 30-day hospital readmission can be predicted. Model performance was assessed using the following metrics: AUC, Accuracy, Precision, Recall and F1 Score. Calibration of predictions were performed using Brier Score. A feature ablation analysis was performed and the change in AUC with the removal of each feature was then assessed to determine feature importance. Results: A total of 10,535 unique surgeries and 10,358 unique surgical elderly patients were included. The overall 30-day unplanned readmission rate was 3.36%. The AUCs of the six machine learning algorithms predicting postoperative 30-day unplanned readmission ranged from 0.6865 to 0.8654. The RF+XGBoost algorithm overall performed the best with an AUC of 0.8654(95%CI, 0.8484 - 0.8824), accuracy of 0.9868 (95%CI, 0.9834 - 0.9902), precision of 0.3960 (95%CI, 0.3854 - 0.4066), recall of 0.3184 (95%CI, 0.259 - 0.3778), and F1 score of 0.4909 (95%CI, 0.3907 - 0.5911); The brier scores of the six machine learning algorithms predicting postoperative 30-day unplanned readmission ranged from 0.3721 to 0.0464, with RF+XGBoost showing the best calibration capability. The most five important features of RF+XGBoost were operation duration, white blood cell count, BMI, total bilirubin concentration, and blood glucose concentration. Conclusion: Machine learning algorithms can accurately predict postoperative unplanned 30-day readmission in elderly surgical patients.